Unsteady Williamson Fluid Flow Over Exponentially Stretching Sheet in the presence of Non-Uniform Heat Generation or Absorption and Inclined Magnetic Field - Akter, R.; Islam, M. A. (Journal of Scientific Research, 2023)
The effect of an inclined magnetic field on unsteady magneto hydrodynamic Williamson fluid flow past an exponentially stretching sheet with joule heating, non-uniform heat generation or absorption, and suction or blowing is investigated numerically in this work. The reduced non-linear ordinary differential equations are obtained from governing partial differential equations using appropriate similarity transformations. The reduced equations are then solved with the help of bvp4c in MATLAB. The effects of various physical parameters on velocity, temperature and concentration profile, skin friction coefficient, Nusselt, and Sherwood number are described through graphs and tables. The result indicates that the rising values of the Weissenberg number decrease the velocity profile and increase the temperature and concentration profiles. It is also found that an inclined magnetic field reduces fluid velocity.